2013
DOI: 10.18321/ectj171
|View full text |Cite
|
Sign up to set email alerts
|

The Laser Active Element Based on Dye on Porous Alumina

Abstract: <p>Luminescent properties of Rhodamine 6G in porous alumina matrix have been investigated. From the SEM images the pore diameter is determined to be ~ 50 nm and the distance between the pores to be about 250 nm. Specific surface area of nanoporous alumina films measured by gas adsorption (BET method) was 6 m<sup>2</sup>/g. Absorption and fluorescence spectra of Rhodamine 6G embedded in pores of anodic alumina oxide were measured. Decreasing of absorbance of monomers was observed upon increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…2D NAA-PCs in the form of slabs developed by Masuda and Yokoyama achieved outstandingly high-quality factors, with values of ∼6838 and ∼6333, respectively. Although 1D NAA-GIFs achieve lasing qualities 1 order of magnitude lower, these PCs provide higher lasing quality than that reported for other 2D NAA-based organic solid-state incoherent random lasing systems, with maximum Q LE and G LE values of ∼125 and ∼10.4, respectively, and a maximum Q LE · G LE value of ∼536. Unfortunately, lasing emissions from 1D NAA-DBRs developed by Yang and co-workers were not characterized and thus a comparison with that study is not possible .…”
Section: Results and Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…2D NAA-PCs in the form of slabs developed by Masuda and Yokoyama achieved outstandingly high-quality factors, with values of ∼6838 and ∼6333, respectively. Although 1D NAA-GIFs achieve lasing qualities 1 order of magnitude lower, these PCs provide higher lasing quality than that reported for other 2D NAA-based organic solid-state incoherent random lasing systems, with maximum Q LE and G LE values of ∼125 and ∼10.4, respectively, and a maximum Q LE · G LE value of ∼536. Unfortunately, lasing emissions from 1D NAA-DBRs developed by Yang and co-workers were not characterized and thus a comparison with that study is not possible .…”
Section: Results and Discussionmentioning
confidence: 59%
“…An alternative approach to overcome this limitation is functionalizing the inner surface of NAA-PCs with layers of light-emitting materials . Masuda and co-workers realized the first organic solid-state lasing systems from model 2D NAA-PC slabs by modifying their inner surface with composite gain medium layers of fluorophores and dendrimersbranched polymeric molecules. These organic solid-state PC structures yield lasing emissions (LEs) with subnanometric bandwidth (i.e., ∼0.08 nm) and giant quality factor (i.e., ∼6330). However, demonstrations of lasing emissions from NAA-based PC structures are still limited to a few studies. 2D NAA-PC lasing systems suffer from two main constraints: (i) coupling and collection of light at the cross section of thin slabs are challenging and (ii) a constrained range of pore diameter and interpore distance within self-organized regimes. In contrast to their 2D counterparts, 1D NAA-PCs would provide more flexible platforms to develop solid-state lasing systems since (i) the range of lattice constant (period length) can be engineered with precision across the broad spectrum from UV to IR (ii) and more forms of NAA-based PC architectures can be realized (e.g., microcavities, DBRs, GIFs, BSBRs) to harness distinct types of light–matter interactions (e.g., light confinement and recirculation, slow light, hybrid plasmonic–photonic modes).…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies by Masuda and co-workers demonstrated slow photon-based organic–inorganic solid-state lasing systems using model 2D NAA slabs functionalized with fluorophores and dendrimers. The PSB of 2D NAA photonic crystals can enhance spontaneous emission by increasing the radiative rate of the gain medium (i.e., fluorophore molecules) through alteration of the dispersion or density of states of emitted photons at the red edge of the PSB (i.e., dielectric component of the porous photonic crystal). Although slow photon lasers based on NAA slabs showed outstanding quality factors (i.e., ∼6330) and ultranarrow bandwidths (i.e., ∼0.08 nm), coupling excitation and the collection of emitted light at the cross section of these thin slabs is challenging. Alternative approaches have focused on the development of distinct forms of RLs combining NAA and organic fluorophores. In these systems, the characteristics of lasing can be engineered in a cavity-free structure by tuning the density of states of the electromagnetic emission through the structural engineering of nanopores (scattering centers). NAA-based RLs (NAA-RLs) also provide operational simplicity because optical excitation and the collection of emitted light can be performed perpendicularly to the cross section of the NAA thin film.…”
Section: Introductionmentioning
confidence: 99%
“…The first experiments on lasing of organic compounds in anodized aluminum films obtained by sol-gel technology with adsorbed rhodamine dyes were performed in [9] under pumping by a pulsed N 2 laser with a pulse duration of 5 ns. Stimulated emission of rhodamine 6G in the porous matrix of anodized aluminum oxide was obtained in [10][11][12]. The effect of various anodizing regimes on the improvement of lasing and radiation quality was not considered.…”
Section: Introductionmentioning
confidence: 99%